ChemInform Abstract: Convenient Synthesis of Spiroindole Derivatives via Palladium‐Catalyzed Cyclization of Propargyl Chlorides. Issue 50 (December 2015) - Iwata, Akira; Inuki, Shinsuke; Oishi, Shinya; Fujii, Nobutaka; Ohno, Hiroaki
Abstract: The cyclization of propargyl chlorides (I) in the presence of benzylamine affords spiroindoles (II), whereas in the presence of sulfonamide (III) and malonate (V) spiroindoles (IV) or (VI) are predominantly formed.